(untitled) (Fiep Bulletin - online, 2013)
This qualitative study tried to evaluate the perspective of 219 children taking part in an educational sports program - Segundo Tempo program, Sports Ministry, regarding the acquirement of parameters concerning three content dimensions (conceptual, procedural and attitudinal) for two pedagogical cycles of five months each. The research instrument for data collection was divided into three scorecards with ten, seven and nine parameters, respectively, therefore twenty-six evaluation parameters. Five scores were considered to evaluate each parameter considering the following classification: score 1 (does not conduct), score 2 (conducts few times), score 3 (conducts sometimes), score 2 (conducts many times), score 5 (always conducts).A performance/competition oriented focus was hardly approached in the program during pedagogical interventions, however we notice great increase in scores for most of evaluated parameters. Results suggest that such improvement may be attached to participation in several modalities (more stimuli to students), essential motor skills training (running, casting, climbing, jumping etc.), casual practices in only one sport (sports monoculture) and no concern towards a perfect motor gesture. It is relevant to highlight that this study did not seek discussions on educational sports primacy as a pedagogical practice in detriment of other methodologies or teaching possibilities such as sports performance, establishing a close relationship with educational sports.